The legitimacy of international organizations - Coicaud, Jean-Marc; Heiskanen, Veijo (Veijo Aulis) (United Nations University Press, 2001)
In the immediate aftermath of the Cold War, international organizations and in particular the United Nations seemed finally capable of redeeming the promise invested in them forty-five years earlier. In the late 1990s, however, the picture was quite different. A number of international organizations had been able to retain or even reinforce their roles and new organizations had been created. On the other hand, the United Nations and other organizations with a 'progressive' rather than market oriented or technical agenda seemed out of vogue. Now, in the early 2000s, the situation has changed again. While the United Nations appears to be less under attack, the international organizations that were the stars of the second half of the 1990s the IMF, the World Bank, and WTO are being challenged and asked to evolve. The end of the Cold War is only one in a series of events that has radically modified the operational environment of international organizations since their establishment. These changes, many of which have lately been discussed under the term 'globalization, ' include: decolonization; growing awareness of the global nature of many economic, environmental, and public health problems; multiplication of non-governmental organizations; globalization of mass media and the market; rapid developments in the field of biotechnology; and the emergence of new information technologies, particularly the Internet. These developments suggest that the time has come to take a fresh look at the philosophy of international organizations. The Legitimacy of International Organizations presents the results of an interdisciplinary research project by the Peace and Governance Programme of the United Nations University. The authors are experts in the fields of law, political science, social and political philosophy, economics, and environmental studies.